The Influence of Transformational Leadership and Compensation on Employee Performance through Work Motivation - Silvia Hendrayanti; Sari, Cahyani Tunggal (Management Analysis Journal, 2024)
Primadana  Yogyakarta  Savings  and  Loans  Cooperative  has  problems  with leadership  style  and  compensation  which  ultimately  affects  employee performance.  It  was  found  that  leaders  were  less  familiar  with  subordinates, leaders  were  more  focused  on  building  relationships  with  superiors  and  less focused  on  subordinates,  and  employees  felt  the  percentage  value  of  each compensation  was  getting  smaller.  The  problems  that  occur  require  further research to be carried out. The purpose of this research is to determine the direct and  indirect  influence  of  Transformational  leadership  and  compensation  on employee  performance  through  work  motivation  at  the  Yogyakarta  Primadana Savings and Loans Cooperative. The population in this study were 62 employees of the Yogyakarta Primadana Savings and Loans Cooperative. The data collection method uses a questionnaire with the data analysis method using the path analysis test  with  the  SPSS  application.  This  research  shows  that  transformational leadership  has  a  positive  and  significant  effect  on  employee  motivation  and performance,  compensation  has  a  positive  and  significant  effect  on  employee motivation  and  performance.  Motivation  mediates  the  influence  of transformational  leadership  and  compensation  on  employee  performance  at  the Yogyakarta  Primadana  Savings  and  Loans  Cooperative.  Companies  must, through  managers/leaders,  strive  to  continue  implementing  a  transformational leadership style and develop work motivation and empowerment for employees, because this has an influence on the performance that will be achieved by company employee.